Utility of platelet indices as a diagnostic indicator of hemodynamically significant PDA in preterm infants: a comparative cross-sectional study - Samar Mahmoud Elbahy; Ola Galal Ali; Sara Soliman Ali; Ali Galal Ali; Eman Gamal Abdelrahman (Egyptian Pediatric Association Gazette)
Abstract Background Among preterm babies, patent ductus arteriosus (PDA) is a prevalent condition, and hemodynamically significant patent ductus arteriosus (hsPDA) constitutes an important problem that impacts their outcome. There has previously been a connection between platelet dysfunction and the hemodynamic significance of PDA. However, the results are conflicting, and more research is warranted. In this study, we investigated the relation of hsPDA with different platelet indices. In addition, we assessed the impact of hsPDA on patient outcomes, including hospital admission and survival rate. Methods This comparative cross-sectional study involved 150 preterm neonates (≤ 34 weeks gestational age) admitted to the neonatal intensive care unit. Following evaluation using the clinical Kindler score, echocardiography was used to confirm the diagnosis of hsPDA. A complete blood count comprising all platelet parameters and C-reactive protein was performed on the first day of life, and the association with the hsPDA was examined. Information was gathered about hospital stay duration, survival rates, and comorbidities. Results Platelet distribution width (PDW) was significantly higher in the hsPDA group than in the non-hsPDA group, p = 0.001. The receiver operating characteristic (ROC) curve analysis revealed a significant correlation of hsPDA with high PDW (p < 0.000) and clinical Kindler score (p < 0.001). High PDW and clinical Kindler score were found to be independent predictors of hsPDA by multivariate logistic regression analysis (odds ratio = 1.289, p = 0.004) for PDW, and (odds ratio = 3.452; p = 0.001) for clinical Kindler score. Regarding patient outcome, the hsPDA group demonstrated significantly longer hospitalization duration and higher respiratory complications and mortality rates. Conclusions PDW and clinical Kindler score were found to be significantly correlated with hsPDA, and both were independent predictors of hsPDA. The hsPDA has dramatically impacted patient outcomes, including higher incidence of respiratory complications, and subsequently longer hospitalization, and higher mortality.